Student Preferences and Rationales for Five Wordwall Game Formats in Arabic Vocabulary Learning - Sukirman Sukirman; Muhammad Nur Kholis (ALSINATUNA, 2025)
This study investigates students’ perceptions of the effectiveness, enjoyment, engagement, and preference in using Wordwall-based activities for learning Arabic vocabulary. Employing a sequential explanatory mixed-methods design, the research involved 38 Arabic language students at an Islamic university who had direct experience using five types of Wordwall-based games, including quiz-based, matching, and puzzle activities. A descriptive survey was first used to map student preferences across the four criteria. Subsequently, thematic analysis of open-ended responses was conducted to explain the quantitative trends. Each game was integrated into vocabulary learning sessions, after which participants completed a questionnaire consisting of four multiple-choice and four open-ended questions. Quantitative data were analyzed using descriptive statistics to determine the frequency and percentage of preferences, while qualitative data were analyzed thematically to explore underlying reasons and insights. Thematic analysis followed the key stages of familiarization, coding, theme identification, and interpretation, focusing on themes such as ease, challenge, reward systems, time, and visual displays. Results indicate that Gameshow Quiz is perceived as the most effective and preferred game, whereas Maze Chase and Find the Match stand out for their interactivity and visual appeal. Overall, the findings emphasize the pedagogical value of game-based learning in enhancing student engagement and vocabulary acquisition in Arabic language instruction.